Effects of treatment with bimatoprost 0.03% for 3 years in patients with normal-tension glaucoma - Inoue, Kenji (Dove Medical Press, 2014)
PURPOSE: To evaluate the effects of bimatoprost 0.03% single treatment for 3 years on intraocular pressure (IOP) and visual field performance. METHODS: We monitored the IOP of 62 patients with normal-tension glaucoma every 1–3 months. The Humphrey visual field test was performed every 6 months after treatment and the results obtained were compared to those before treatment. In addition, visual field performance was evaluated using trend and event analysis. RESULTS: The mean ± standard deviation (SD) of IOP after treatment with bimatoprost for 3 years (13.6±3.1 mmHg) was significantly lower than that before treatment (16.8±2.4 mmHg, P<0.0001). No change was observed in the mean deviation and pattern SD values of the Humphrey visual field before and 3 years after treatment. Worsening of visual field performance was observed in one patient (3.0%) by using trend analysis and in four patients (12.1%) by using event analysis. Treatment was discontinued in 17 patients (27.4%) because of adverse reactions. CONCLUSION: Bimatoprost 0.03% single treatment was effective in reducing the IOP at least during the 3 years of treatment, but visual field performance worsened by 3.0%–12.1% in patients with normal-tension glaucoma.